2015
DOI: 10.1007/s00404-015-3909-5
|View full text |Cite
|
Sign up to set email alerts
|

Is endometrial ablation protective against endometrial cancer? A retrospective observational study

Abstract: To our knowledge, this is the largest study to examine the long-term incidence of endometrial cancer in women who had endometrial ablative procedures. It shows that the development of endometrial cancer does not seem to be associated with endometrial ablative procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…However, the study provided an insufficient surveillance period and was composed of a group of women whose average age was 56 ± 6 years, well short of the mean age at which EC typically presents. Finally, a more recent study by Singh et al 41 conducted in the United Kingdom included 1521 women who underwent various types of EA procedures between 1994 and 2011 and noted that none of the women in this retrospective observational study developed EC during the surveillance period. Their suggestion that EA may even have a protective effect on the development of EC is unsupported by their data and the study's design.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the study provided an insufficient surveillance period and was composed of a group of women whose average age was 56 ± 6 years, well short of the mean age at which EC typically presents. Finally, a more recent study by Singh et al 41 conducted in the United Kingdom included 1521 women who underwent various types of EA procedures between 1994 and 2011 and noted that none of the women in this retrospective observational study developed EC during the surveillance period. Their suggestion that EA may even have a protective effect on the development of EC is unsupported by their data and the study's design.…”
Section: Discussionmentioning
confidence: 83%
“…45,46 Simultaneously, the widespread implementation of EA in the United States 14,15,26 and other industrialized countries within the past 20 years means that a large population of EA-treated women, now entering their sixth and seventh decades of life, are at an increasing age-related risk of developing EC. Several researcher-surgeons have suggested 24,25,40,41 that EA does not affect the stage at which EC presents. However, the increasing use of this modality and the shift from NREA to global EA requires larger prospective long-term studies to adequately understand this question.…”
Section: Resultsmentioning
confidence: 99%
“…The study provided strong evidence based on long‐term follow‐up that EA/R considerably reduces the risk of endometrial among women treated for menorrhagia, highlighting the importance of this very common treatment method. By contrast, other studies have concluded that EA/R neither increases the risk of endometrial nor prevents early diagnosis owing to masking of symptoms or technical difficulties associated with performing hysteroscopy and biopsy …”
Section: Discussionmentioning
confidence: 85%
“…By contrast, other studies have concluded that EA/R neither increases the risk of endometrial nor prevents early diagnosis owing to masking of symptoms or technical difficulties associated with performing hysteroscopy and biopsy. 2,[9][10][11][12] A literature search of publications in the English language identified 17 reported cases of endometrial after EA/R with adequate data on clinical and demographic characteristics 5,[21][22][23][24][25][26][27][28][29][30][31] (Table 2). However, F I G U R E 1 Rate of uterine corpus cancer stratified age group in Scotland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation